O Cineclube Antônio das Mortes: trajetória, exibição e produção (1977-1987) - Campos, Marina da Costa (2014)
This research analyses the history of the Cineclube Antônio das Mortes, CAM, between 1977 and 1987. This organization was created in the city of Goiânia and its main activities were film screenings, discussions, study groups, film criticism and audiovisual production. Through the survey of documents, newspapers, photos, testimonials and films, it was possible to focus on three aspects of the historical process of this cine-club: The first one is its trajectory, including the study of its exhibitions, discussions after screenings, study groups and the characteristics the entity acquired during ten years of activities. The second aspect is the comprehension of CAM while a cine-club, and its relationship with the cine-club movement in Brazil. The third aspect is the film production and the film criticism by its members. This research has the main objective of identifying the various profiles that the cine-club acquired and how they had had strong influence over the relation with other cineclubs and the film criticism and the audiovisual production of the group.